Factors Associated With Sense of Efficacy Among First Year Teachers in Sarawak - Murshidi, Rahmah (2005)
This study aimed at examining factors associated with sense of efficacy among first year beginning teachers in Sarawak, Malaysia. Beginning teachers are newly and hlly qualified teachers in their first three years of teaching assignment. The aim of this study was pursued by: (a) examining the correlation between two contextual variables (support system and school climate) and first year teachers' sense of efficacy; (b) investigating the differences in sense of efficacy in relation to selected demographic variables; and (c) identifying the predictors of first year teachers' sense of efficacy from the independent variables. This study employed a combination of both quantitative and qualitative methods. Quantitative method was set to examine the associating factors while as qualitative method was utilised to support and triangulate the association. The quantitative data were gathered by survey method using three instruments: Teacher Sense of Efficacy Scale (Tschannen-Moran & Woolfolk Hoy, 2001), Support System Survey (a selfdesigned instrument) and School Climate Index (Tschannen-Moran & Parish, 2003). Semi-structured interviews were employed to gather qualitative data. The questionnaires were administered to a sample of 328 first year teachers from 45 secondary schools in Sarawak. The subjects of the study were selected by using stratified random sampling according to eight Educational Administrative Divisions in Sarawak and locality of the schools (urban and rural). The interviews were conducted with two Principals, two Administrative Senior Assistants and six first year teachers from three secondary schools. Two schools with the highest efficacy mean score and one school with the lowest mean score were selected from research sample to be the sites to conduct the interviews. The quantitative findings indicated that first year teachers demonstrated a moderate level of teachers' sense of efficacy (M = 6.57, SD = 30; score range from 1 to 9), perceived they were provided with a moderate level of support system (M = 3.32, SD = .57; score range from 1 to 5) and perceived their schools have a moderate positive school climate (M = 3.66, SD = .49; score range from 1 to 5). The correlation was significant and moderately positive between support system and first year teachers' sense of efficacy (r = .40, p < .01) and between school climate and first year teachers' sense of efficacy (r = .3 1, p < .01). Qualitative analyses provided related evidence to support and triangulate the correlation between the variables. There were significant differences in first year teachers' sense of efficacy in relation to types of teacher education (t = -2.35, p < .05), oral English proficiency (F [2, 3251 = 4.30, p < .05) and ethnicity (F [3, 3241 = 3.88, p < .05). There was no significant difference in first year teachers7 sense of efficacy in relation to gender (t = 1.42, p > .05), schools location (t = -.08, p > .05), having teaching experience (t = -1.28, p > .05), age groups (F [3,324] = 35, p > .05), and teaching subject option (F [2,325] = 2.52, p > .05). Two factors from the variable support system (instructional support and institutional support) and one factor from the variable school climate (academic press) were identified as the predictors of teachers7 sense of efficacy (R* = .205, F [3, 3241 = 27.766, p < .001). The implication of the stpdy on the theory and practice of teachers' sense of efficacy was discussed. Suggestions were offered as considerations to enhance and foster senses' of efficacy among the first year teachers.